ANALYSIS OF ISLAMIC ORGANIZATIONAL CULTURE IN FOSTERING ORGANIZATIONAL INNOVATION ON RABBANI HOLDING, BANDUNG - Ratih Purbasari; Nurillah Jamil Achmawati Novel (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2016)
This study raised concerns about the Islamic culture on Rabbani Holding, which has been widely known as a company that produces products of Islamic fashion in Bandung and has received awards from various institutions. Nevertheless, Rabbani  keep innovating organization driven by company dynamic and its cultural values. Research on islamic culture at a fashion company area  is still rare in Bandung due to fashion business itself has been just rapidly growing in recent years. Thus, it becomes very interesting subject to study, especially if associated with organizational innovation. This study used qualitative research methods through extracting information (interviews) in depth, literature, and field observations. Data processed by the coding technique and analyzed descriptively. The results showed that Islamic organizational culture in Rabbani Holding has been implemented consistently and continously evolving. Islamic culture which has been applied in Rabbani is fundamental in driving performance in all its business functions, where its culture consists of consumer focus, employee focus, quality focus and organization focus which includes the core values of Rabbani organizational  innovation.